Fasting does not induce gastric emptying in rats - Brito,Marcus Vinicius Henriques (2015)
PURPOSE: To evaluate the effect of fasting on gastric emptying in mice.METHODS:Twenty-eight mice were distributed into three study groups: a normal group (N=4): normal standard animals; a total fasting group (N=12): subjected to food and water deprivation and a partial fasting group (N=12): subjected to food deprivation only. The fasting groups were subdivided into three subgroups of four animals each, according to the date of euthanasia: 24, 48 and 72 hours. Was analyzed: the gastric volume, degree of the gastric wall distention and the presence of food debris in gastrointestinal tract.RESULTS:The mean gastric volume was 1601 mm3in the normal group, 847 mm3in total fasting group and 997 mm3in partial fasting group. There was difference between the fasting groups in any analyzed period (p<0.05). Regarding the presence of food debris in the gastrointestinal tract and the degree of distension of the stomach, there was no difference between the groups that underwent total or partial fasting (p>0.05).CONCLUSION:Total fasting or only-solids deprivation does not induce gastric emptying in mice.